Plympton Priory : a house of Augustinian Canons in south-western England in the late Middle Ages - Fizzard, Allison D. (Brill's series in church history ;, 2008)
A case study which examines the history of a house of English Augustinian canons. This book reveals the ways in which Plympton Priory formed connections with the laity, the episcopacy, the secular clergy, and the Crown in the late Middle Ages.